Implementasi Azas Kerahasiaan dalam Layanan Konseling di Sekolah Menengah di Indonesia : Sebuah Studi Deskriptif - Mudjijanti, Fransisca; Nugroho, Felix Trisuko (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2025)
Students as individuals and students are faced with various problems that will affect their learning process. Counseling as the heart of the guidance program is an effort to help solve student problems. One aspect of the success of counseling services is the application of the principles of guidance and counseling. There are 12 principles in guidance and counseling services, and the principle of confidentiality is the most important principle, because it is a key principle. If the principle of confidentiality is truly implemented, the counselor will gain the trust of all parties, especially the counselee. This research aims to obtain an overview of the implementation of the principle of confidentiality in counseling services at schools. The research method uses an online survey method. The research population was junior and senior high school students in Indonesia for the 2024/2025 academic year. The research sample of 664 was determined using the Lemeshow formula.  The sampling technique uses the Quota Sampling technique. The research instrument uses a questionnaire in the form of a scale. The data analysis technique uses descriptive statistics. The research results show that the implementation of the principle of confidentiality in counseling services is in the very poor category 6.5%, in the poor category 9%, in the quite good category 57.7%, in the good category 16.9%, in the very good category 9.9%.